2006
DOI: 10.1095/biolreprod.105.047969
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Regulation of Follicle-Stimulating Hormone Signaling and Bone Morphogenetic Protein System in Human Granulosa Cells1

Abstract: Bone morphogenetic proteins (BMPs) play critical roles in folliculogenesis by modulating the actions of follicle-stimulating hormone (FSH) in the ovary. However, the effects of FSH on the BMP system remain unknown. Here, we have investigated the effects of FSH on BMP signaling using the human granulosa-like tumor cell line KGN. KGN cells express BMP type I and type II receptors and the BMP signaling molecules SMADs. FSH administration upregulated BMP type IA (BMPR1A) and IB (BMPR1B) receptors, activin type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…In bovine granulosa cells, estrogen used alone and in combination with FSH has been shown to up-regulate BMPR2 mRNA expression [22,24]. Supporting this finding, a study using a human granulosa-like tumor cell line showed that FSH up-regulated BMPR2 in GCs [23]. Our results indicate the likelihood that BMPR2 expression might be up-regulated by rFSH alone or in combination with steroids in PCOS cumulus cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In bovine granulosa cells, estrogen used alone and in combination with FSH has been shown to up-regulate BMPR2 mRNA expression [22,24]. Supporting this finding, a study using a human granulosa-like tumor cell line showed that FSH up-regulated BMPR2 in GCs [23]. Our results indicate the likelihood that BMPR2 expression might be up-regulated by rFSH alone or in combination with steroids in PCOS cumulus cells.…”
Section: Discussionsupporting
confidence: 76%
“…However, a positive correlation was observed between mRNA expression of BMPR2 in PCOS cumulus cells and levels of testosterone and androstenedione in FF from pre-ovulatory follicles. In fact, several studies have shown that BMP receptors are hormonally regulated [22][23][24]. PCOS-related hyperandrogenism can exerts complex effects on the ovarian follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMPR1B is a BMP family member that regulates follicular development by affecting granulosa cell proliferation and steroidogenesis. BMPs modulate FSH actions in the ovary and reciprocally (Miyoshi et al 2006). BMPR1B is expressed from secondary to atretic follicles and is the receptor for BMP2, -4, -6, and -7.…”
Section: Gene Analysismentioning
confidence: 99%
“…In addition, FSH increased the expression levels of SMAD1/ 5 and decreased the expression of inhibitory SMADs, SMAD6/7. Thus, it is most likely that FSH augments the bioavailability of BMP signaling in human granulosa (Miyoshi et al 2006).…”
Section: Introductionmentioning
confidence: 99%